Service Innovation: A Service-Dominant Logic Perspective1 - Lusch, Robert F.; Nambisan, Satish (MIS Quarterly, 2015)
In this article, we offer a broadened view of service innovation—one grounded in service-dominant logic—that transcends the tangible–intangible and producer–consumer divides that have plagued extant research in this area. Such a broadened conceptualization of service innovation emphasizes (1) innovation as a collaborative process occurring in an actor-to-actor (A2A) network, (2) service as the application of specialized competences for the benefit of another actor or the self and as the basis of all exchange, (3) the generativity unleashed by increasing resource liquefaction and resource density, and (4) resource integration as the fundamental way to innovate. Building on these core themes, we offer a tripartite framework of service innovation: (1) service ecosystems, as emergent A2A structures actors create and recreate through their effectual actions and which offer an organizing logic for the actors to exchange service and cocreate value; (2) service platforms, which enhance the efficiency and effectiveness of service exchange by liquefying resources and increasing resource density (facilitating easy access to appropriate resource bundles) and thereby serve as the venue for innovation; and (3) value cocreation, which views value as cocreated by the service offer(er) and the service beneficiary (e.g., customer) through resource integration and indicate the need for mechanisms to support the underlying roles and processes. In discussing these components, we consider the role of information technology—both as an operand resource and as an operant resource—and then examine the implications for research and practice in digitally enabled service innovation.